Theoretical Foundations of Migration Policy (Economics and region, 2021)
The article is devoted to the definition of one of the typical features of the modern era - an increase in the scale, a variety of types and directions of international migration. International movements of the population have become an important factor in social transformations in countries of destination and origin of migrants, and affect interstate relations. These conditions have led to an increase in the importance of migration policy as an obligatory component of the activities of national governments, interstate associations, and the entire world community. As a result, the relevance of scientific research on migration policy, which has theoretical and practical significance, has increased.
Keywords: migration policy; theoretical models; directions of analysis